Landuse Changes Refer to Spatial Planning Regulations at Kelara Watershed Area: An Analysis Using Geospatial Information Technology - Ramlan, Andi; Neswati, Risma; Baja, Sumbangan; Nathan, Muhammad (Forum Geografi, 2015)
The purpose of this study is to analyze land use changes in the Kelara watershed and to assess the suitability of current land use changes with the spatial planning regulation of Jeneponto within Kelara basin. This study integrates various survey techniques, remote sensing, and geographic information system technology analysis. Geospatial information used in this study consists of Landsat ETM 7+ satellite imagery (2009) and Landsat 8 (2014) as well as a number of spatial data based on vector data which is compiled by the Jeneponto Government. Remote sensing data using two time series (2009 and 2014) are analyzed by means of supervised classification and visual classification.Â  The analysis indicated that land use type for the paddy fields and forests (including mangroves) converted become a current land use which is inconsistent with the spatial planning regulation of Jeneponto.The use of land for settlement tends to increase through conversion of wetlands (rice fields). These conditions provide an insight that this condition will occur in the future, so that providing the direction of land use change can be better prepared and anticipated earlier.